PENGARUH PROFITABILITAS, DEBT DEFAULT, PERTUMBUHAN PERUSAHAAN DAN OPINI AUDIT TAHUN SEBELUMNYA TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2016-2020 - Linda Safira Widyarti; Hetty Muniroh (JISOS: JURNAL ILMU SOSIAL, 2022)
This reseach purpose to determine the effect of profitability, debt default, company growth and audit opinion in the previous year on going concern audit receipts for mining companies listed on the Indonesia Stock Exchange in the period 2016-2020. The independent variable of this study are profitability, debt default, company growth and audit opinion in the previous year, while the dependent variable is going concern audit opinion. Population in this study are mining companies listed on the Indonesia Stock Exchange in the period 2016-2020. Sampling was carried out using purposive sampling method and obtained as many as 29 mining companies used as samples in the period 2016-2020, so that the data studied were collected as many as 145. The data analysis techniques used descriptive statistics and logistic regression analysis. The results showed that profitability and company growth had a sizgnificant negative effect on going-concern audit opinion, while debt default and previous year audit opinion had a significant positive effect on going-concern audit opinion